Producing speed Moulting in Mud Crab (Scylla serrata) with Soft Shell Ablation And Mutilation Method - Nurmadina '; Mulyadi '; Usman M. Tang (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in March-May 2014 in the Business Unit GroupSustainable Aquaculture Fisheries, Environment XX Kampung Sentosa West,Village Sicanang Belawan, Medan Belawan subdistrict, Medan. The method usedis an experimental method by using RAL with 3 levels factors and threereplication of control treatment (without ablation and mutilation), ablation, andmutilation. Data were analyzed using ANOVA (P <0.05). Test materials wereused as many as 9 mud crabs were maintained in a single room system takirbamboo of 15 x 15 x 10 cm3 of each partition. Takir bamboo is used as much as 9plot. The results showed that the application of different methods of treatment(ablation and mutilation) was highly significant in accelerating moulting, theaverage absolute carapace length and width, the growth of absolute weight, dailygrowth rate, and survival. The results showed that treatment of mutilation hasbetter effect to accelerate the molting than other treatments with an average speedof moulting 23 day 7 hours 55 minutes 2 seconds. In the treatment of acquiredgrowth mutilation absolute weight (50 grams), growth in absolute length (0.57cm), daily growth rate (1.82%), survival (100%).Keyword : Mud crab, Moulting, and Growth